Doubtful Testimonies of Mr. Leeuwenhoek: Microscopes, Analogies, and Good Neighbours - Špeldová, Monika (Teorie vědy / Theory of Science, 2016)
The aim of the study is to discuss the early microscopic examination of nature, introduced by Antoni van Leeuwenhoek (1632-1723) in his letters to the Royal Society. The paper focuses on period from the establishing of contact with the Royal Society (1673) to the electing of Leeuwenhoek the member of the Society in 1680. From the methodological point of view the study uses the approach which Steven Shapin a Simon Schaffer presented in their book Leviathan and the Air-Pump (1985). The study tries to find out to what extent it is possible to understand Leeuwenhoek's letters as expressing three technologies (material, literary, and social) proposed by the British authors. The paper shows that the Shapin's and Schaffer's understanding of experimental science of Robert Boyle is transferrable to other scientists.